Designing universal component on PLD - Лісовий, О. М.; Опанасенко, В. М.; Сорока, Є. В. (Problems of Informatization and Control, 2009)
The universal components on PLD-based of type FPGA for convert formats of digit are designed. It’s used behavior and mixed descriptions on VHDL for conveyor architecture of components. For checking components work it’s used modeling method in system ModelSim Xilinx Edition - MXE III with the help of the verifying stand and file of input influence